Health Seeking Behaviour by Cape-Townians: A mini-research by first year student nurses at a College for Nursing in Cape Town - S. Haegert (AOSIS, 1996)
The author was asked by a student nurse to use South African examples when teaching, as the textbooks were either American or English, and they wanted sociology that applied to their own environment. In the next year of teaching the prescribed objectives concerning "Health Seeking Behaviour", it was suggested that the students question the populace, and find out for themselves how South Africans behaved when they thought they were ill. By doing this it was hoped that it would also give deeper insights into the meaning people attributed to illness/sickness.